Carbon Capture And Storage (Ccs) - Enhanced Oil Recovery (Eor): Global Potential In Indonesia - Utomo Pratama Iskandar; Ego Syahrial (Scientific Contributions Oil and Gas, 2009)
Total global CO2 emissions from fossil-fuel will still increase in the next ten decades. These are attributed to the heavy reliance of human activities with fossil fuels. The uncontrolled CO2 emissions from combustion of fossil fuels cause the CO2 concentration alteration in the atmosphere. As the result, this phenomenon cause global warming and change the climate globally. In the future, CO2 emissions are predicted in range from 29 to 44 GtCO2/year in 2020. Therefore it is necessary to abate the CO2 Â missions to the level that would prevent dangerous anthropogenic interference to the global climate system. The growth of energy efficiency improvements, the switch to less-carbon intensive fuels and renewable resources employment is still low in the context CO2 emissions mitigation. Carbon Dioxide Capture and Storage (CCS) as a third option for these mitigation options might facilitate achieving CO2 Â missions stabilization goals. As a part of the commitment and participation on combating the global warming, Indonesia has signed the Kyoto Protocol in 1998 and ratified it in 2004 through Law No. 17/2004. On the other side, Indonesia oil production has been declining since in the last ten years but demand for this energy is still high. In this frame CCS-Enhanced Oil Recovery (EOR) by CO2 injection might answer the global warming challenges and alongside contribute to increase the oil production in the near future. This paper presents a preliminary study of CCS-EOR potential in Indonesia. A brief explanation of geological setting and reservoir screening for site selection also presented. Then some discussions about CCS-EOR global potential will be highlighted as well as the analysis. It is hoped that this study would provide a standard guideline for determining CCS- EOR potential in Indonesia.